2011
DOI: 10.1016/s0960-9776(11)70297-1
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer and microRNAs: therapeutic impact

Abstract: Despite advances in detection and therapies, breast cancer is still the leading cause of cancer death in women worldwide. The etiology of this neoplasm is complex, and both genetic and environmental factors contribute to the complicate scenario. Gene profiling studies have been extensively used over the last decades as a powerful tool to define the signature of different cancers and to predict outcome and response to therapies. More recently, a new class of small (19-25 nucleotides) non-coding RNAs, microRNAs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 81 publications
0
79
0
4
Order By: Relevance
“…Understanding of the potential tumor-initiating roles of miRNAs may undoubtedly open the door to new cancer therapies (Schwabe and Wang, 2011). There were numerous reports based on various experiments that suggest the use of miRNAs as both targets and tools in anticancer therapy (Dong et al, 2010;Iorio et al, 2011;Kim et al, 2012), among of which let-7a has been Representative images of the assays (left panel) showed the cells that passed through the membrane and bar graphs (right panel) showed the cell numbers. *p < 0.05, **p < 0.01, ***p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding of the potential tumor-initiating roles of miRNAs may undoubtedly open the door to new cancer therapies (Schwabe and Wang, 2011). There were numerous reports based on various experiments that suggest the use of miRNAs as both targets and tools in anticancer therapy (Dong et al, 2010;Iorio et al, 2011;Kim et al, 2012), among of which let-7a has been Representative images of the assays (left panel) showed the cells that passed through the membrane and bar graphs (right panel) showed the cell numbers. *p < 0.05, **p < 0.01, ***p < 0.001.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, miRNA expression signatures are considered to be promising predictive and prognostic biomarkers for BC (10,11). Increasing studies independently reported onco-miR such as miR-21, miR-210 were over-expressed in BC and the expression levels correlated with tumor aggressiveness and poor prognosis (12).…”
Section: Original Articlementioning
confidence: 99%
“…64 Several other vector-based miRNAs delivering strategy have been developed to restore tumour suppressor or silence oncomiRNAs. 65 An elegant approach, the miRNA Sponge that inhibits miRNA activity for entire miRNA family by saturating them with target mRNAs has been developed by Ebert et al 66 These plasmid vectors encode for mRNAs containing multiple tandem binding sites for endogenous mRNAs. Thus, during the cell miRNA processing, the Sponge interacts with the corresponding miRNA and prevents the association with the mRNA targets.…”
Section: Mirnas As Clinical Biomarkers and Potential Therapeutic Targmentioning
confidence: 99%